Expression, characterization, and rational design of chalcone synthase from Physcomitrella patens - Zakaria, Iffah Izzati (2013)
Flavanoids are plant secondary metabolites synthesized by polyketide synthase (PKS) in plants, fungi and bacteria. The members of the chalcone synthase (CHS) superfamily, also known as the type III PKSs, function as the key entry enzyme of the flavonoid biosynthesis. Flavanoids are found in liverworts and mosses (bryophyte) that are thought to be the land plants ancestor. Although hundred of CHSs genes from various plant species have been successfully clone, expressed and studied, limited information is available on the CHS from the bryophytes. The model moss, Physcomitrella patens is currently the only bryophyte whose genome has been sequenced and its genome contains at least 17 putative type III PKS genes. Among them, a CHS gene was shown to be basal to all plant type III PKS genes in phylogenetic trees. P. patens CHS exhibited similar kinetic properties and substrate preference profiles as those of higher plants. This suggest that the P. Patens CHS may exhibit similar mechanism as the other land plants CHSs. Due to the unavailability of the P. Patens CHS crystal structure, the main aim of this work is to gain some insight on the structure and mechanism of the P. Patens CHS. Apart form the unavailability of P. patens CHS crystal structure, the major bottleneck of this work is to obtain the P. patens CHS due to the slow plant growth rate and low (less than 1%) extraction yield. Therefore, to speed up the process of obtaining the enzyme, the P. patens CHS has been successfully cloned and expressed in E. coli strain BL21 (DE3) plysS. However, the formation of inclusion bodies has become a major disadvantage of this approach. As alternative, P. patens CHS was secreted into the medium using a bacteriocin release protein expression vector. Secretion of P. patens CHS into the culture media was achieved by co-expression with a psW1 plasmid encoding bacteriocin release protein in E. coli Tuner (DE3) plysS. The optimized conditions were incubation of cells for 20 hours with 40 ng/ml mitomycin C at OD600 induction time of 0.5 was found to be the best condition for chalcone synthase secretion. The recombinant P. patens CHS was purified to 1.78-fold with 88.1% yield and specific activity of 4.26 U/mg by affinity chromatography technique using Ni 2+ Sepharose Fast Flow resin. The enzyme optimum pH and temperature were 7.0 and 30 °C, respectively. In addition, the enzyme was found to be stable up to 50 °C. Several crystallization attempts of P. patens CHS was carried out using vapour diffusion techniques, however, X-ray data processing was unable to be performed due to the weak diffraction spots obtained from the P. Patens crystals. Weak diffraction spots obtained might be due to poor crystal packing, the presence of impurities, nonspecific aggregations and crystal damaged by X-ray beam. Consequently, to study the structure and mechanism of P. patens CHS, combination of homology modeling and site-directed mutagenesis was conducted. The P. patens CHS structure was built using the M. sativa CHS crystal structure as a template. Based on the overall assessment, the quality of the modeled structure was comparable to template. Through the modeled PpCHS structure, showed the same four catalytic residues of the active site conserved in other CHS superfamily. Due to the function of the catalytic Cys170 in the first binding (initiation reaction) of the starter molecule on the catalytic active site, it was targeted as a critical residue. To investigate the effect of Cys170 substitutions towards the P. patens enzyme activity, two mutants were constructed, C170 R and C170S. From the mutant‟s data analysis, it could be concluded that the catalytic residue Cys170 plays an important role in the binding of substrate onto the active site. Substitution of Cys170 has lead to several changes in its interaction among the other residues resides in the active site cavity. The changes affect the binding capacity, cavity volume of the active site and the overall protein structure volume which decreased the production of reaction products. Apart, the mutant‟s physical properties such as temperature, pH and stability were found to be affected as well.